KEBIJAKAN PEMERINTAH DAERAH DALAM PELAKSANAAN PENDIDIKAN DI KABUPATEN KONAWE - Hartono Hasim (Prodi Ilmu Hukum, Universitas Teuku Umar, 2021)
Context of the implementation of education in Konawe there are many problems arise. Understanding and strong commitment from the local government is very necessary in order to answer the existing constraint. This can be seen in the formulation of legislation. As expressed in Article 2 of Law No. 20 of 2003 that: